Fiscal incentives and tax compliance behaviour in industrial clusters: A survey of clusters in South-East Nigeria - Ebele Stella Nwokoye; Clement Izuchukwu Igbanugo; Chukwunonso Ekesiobi; Stephen Kelechi Dimnwobi (African Governance and Development Institute (AGDI), 2022)
The study investigates the impact of fiscal incentives on the tax compliance behaviour of firms in industrial clusters in Nigeria. Data from 800 firms drawn from three industrial clusters in SouthEast Nigeria were collected using a structured questionnaire through a multi-stage sampling procedure. Descriptive statistics and the logistic regression model were applied to estimate the survey responses.The major findings of the study show that regular tax audit, firm size, simplifying the communication on tax requirement, communicating deterrent messages, educational attainment of the firm owner and political legitimacy of the current government as well as fiscal incentives (tax credit, tax reduction, capital allowance, investment incentives) significantly influence the tax compliance behaviour of firms in Nigeria's industrial clusters. Similarly, the study finds that fiscal incentives significantly enhance firm performance in Nigeria's industrial clusters. Implications and policy suggestions are presented for adoption by concerned stakeholders in the tax and industrial sectors.
Keywords: 330; Fiscal incentive; Tax compliance; Industrial Cluster; Nigeria